LES MASS MEDIA FACE AU DEFI DU DEVELOPPEMENT LOCAL : LA RADIO RURALE LOCALE DE TANGUIETA A L’EPREUVE DES FAITS - OUASSA, KOUARO MONIQUE; TASSO, Florent B.; YANTEKOUA, Boni (My University, 2013)
This reflection analyzes the place of mass media in front of challenge of the local development. The analysis of empirical data collected with 130 persons selected by reasoned choice, reveals that the local rural radio of Tanguiéta allows to inform and to educate an essentially rural community, to which it gives the ways to make decisions informed with the aim of the improvement of their quality of life.
Keywords: Mass media; local rural radio; local development; Tanguiéta